Science Diplomacy in the Arctic and Antarctic - Valeriy N. Konyshev (Арктика и Север, 2023)
The article studies the phenomenon of science diplomacy with regard to the Arctic and Antarctic. These two polar regions are similar because of high importance of international scientific activity and science diplomacy based on it. Science diplomacy is understood as a kind of synthesis of scientific and political-diplomatic activities, in which state and non-state actors can take part. The conditions for science di-plomacy in the Arctic and Antarctic are very different due to the history of development, legal status and established practice of international relations in these regions. The challenges faced by international scientific activity and science diplomacy in the two regions are considered. It is shown that in the Arctic and Antarctic, science diplomacy as a political tool is objectively in demand and cannot be “cancelled” due to the political context. In the current situation, science diplomacy can contribute to de-escalation of the conflict in relations between Russia and the West. At the same time, science diplomacy is not a panacea for creating international relations based on the principles of peace and cooperation. Like any political instrument, it protects national interests and not only serves to solve global problems arising in the Arctic and Antarctic.